The identity of the semiterrestrial crab Terrathelphusa kuchingensis (Nobili, 1901) (Crustacea: Decapoda: Brachyura: Gecarcinucidae), with descriptions of four new species from southwestern Sarawak, Borneo, Malaysia - Grinang, Jongkar; Ng, Peter K. L. (Zootaxa, 2015)
Four new species of semiterrestrial gecarcinucid crabs are described from limestone and sandstone habitats in southwestern Sarawak, Malaysia: Terrathelphusa aglaia n. sp., T. cerina n. sp., T. kundong n. sp., and T. mas n. sp. The taxonomy of T. kuchingensis (Nobili, 1901) is discussed, its precise identity ascertained from fresh material, and its actual distribution determined. This increases the number of Terrathelphusa species in Borneo to eight.